Effect of Genistein on Heat Shock Protein 47 and Collagen Type IV in Diabetic Rat - Putri Dafriani; Nur Indrawati Lipoeto; Yanwirasti; AmriBakhtiar; Roza Marlinda (Journal of Pharmacy and Nutrition Sciences, 2018)
Diabetes nephropathy (DN) is one of the most common complication in Diabetes Mellitus (DM). DN is an inflammatory process which involved immune cells and effect of genistein prevent this mechanism. However, the effects on HSP 47 and collagen type IV are not yet verified. The purpose of this study was to investigate whether the genistein can suppress HSP 47 and collagen type IV. This study is experimental design used 25 rats. Rats were divided into five groups; normal group, hyperglycemia group, hyperglycemia by administering genistein 0.5 mg/kgw, 1mg/kgw, and 2 mg/kg. Streptozotocin induced 65 mg/kg administered intraperitoneal. Treatment duration is 4 weeks. After 4 weeks of blood was collected via the orbital vein and examined the levels of HSP 47 then rats’ kidneys were taken to see the levels of collagen type IV. The average levels of HSP 47 in non diabetic control group was 1.7982 ng/ml, diabetic control 7.9424 ng/ml, STZ; G 0.5 mg/kgw 5.4192 ng/ml, STZ; G 1 mg/kgw 3.1152 ng/ml and STZ; G 2 mg/kgw 1.849 ng/ml, with p value 0.000 (p<0.05). While Type IV Collagen in non diabetic group was 10.006 ng/ml, diabetic group 26.864 ng/ml, STZ: G 0.5 mg/kgw 21.426 ng/ml, STZ; G 1 mg/kgw 17.352 ng/ml and STZ; G 2 mg/kgw 13.436 ng/ml with p value 0.000 (p<0.05). Administer the genistein can reduce levels of HSP 47 and collagen type IV in diabetic rats. Genistein can reduce fibrotic mediators induced by NFkB and MAPK signaling by inhibiting the tyrosine kinase protein activation.